(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The article discUsses the results of empirical ’studies on the application of penal law provisions concerning abortion in the Federal Republic of Germany which were amended in 1976. The studies concentrated, first of all, on the application of sanctions provided for by the provislions, i.e. the problem which had not been so fair dealt with. The following problems were analyzed in detail: the application of norms by prosecution organs, the iinflueince of application of norms on abortion on women’s attitudes and dedisions, and the role of a doctor In the application of the provisions as well as motives, reasons and effects of the interest of social groups in the question of stages of establishing and applying the norms in the discusses field. It has been pointed out that the basic withdrawal from the control by penal law of abortion took place much earlier, i.e. ait the end of the 60s. The further decrease of revealed illegal abortions and convictions observed after the amended provisions on abortion came into force, had practically no meaning. First of all, it has been admitted that the present application of the system of sanctions concerning aboration allowS to define it as "criminal incidental law" and to postulate penalization by the constitution is disputable if the system of sanctions is not appropriately applied and closely connected with the interests protected by law. The latter issue is of a particular dmportante because in neighbouring states abortion is legal., The present conflict between breaking down penalization aims and possibilities of achieving them may bring about permanent group and individual conflicts. Therefore, inaccurate definition of the scope of indication, especially social one, is particularly startling. Therefore sanctions concerning abortion cannot fulfil their preventive functions, the more so as appropriate social norms and system of social control directly resulting from them are not advanced yet. The author also stresses IseriouS difficulties in case when the object of studies are decisive /processes connected with abortion,